Bactericidal potential of two species typical of Brazilian cerrado: Stryphnodendron obovatum and Lafoensia pacari - Dos Santos, Rodrigo Martins [UNESP]; Ferraz, Diego Emanuel; Neto, Maria José; Bernardes, Luiz Gustavo; Brito, Vinícius Martins; Gelle-Oliveira, Glória Maria (My University, 2019)
This study aimed to evaluate the bactericidal potential of plant extracts from medicinal plants of the Brazilian cerrado against microorganisms associated with gastrointestinal infections, through the disc-diffusion method. Two typical cerrado plants were selected: Stryphnodendron obovatum and Lafoensia pacari. The leaves were crushed and reduced to the powder state, and for the extraction of substances 100% methanol was used as the solvent followed by the proportion of 1 g and 2 g of vegetable powder 10 ml of solvent [extracts 1:10 and 2:10 (p/v)] and the microorganisms submitted to the test were Escherichia coli, Staphylococcus aureus and Klebsiella sp. The results showed that L. pacari presented a better percentage of bactericidal activity by the disc-diffusion method in all microorganisms tested with inhibition halos between 15 and 20 mm in both concentrations; S. obovatum showed only antimicrobial activity in S. aureus cultures at both concentrations with inhibition halos between 12 and 16 mm. Both species present great possibilities of being useful in the fight against multiresistant bacteria, allowing the investigation and the isolation guided by bioassays as well as the future identification of new bioactive compounds. It’s concluded that it is necessary to fill gaps related to the scientific knowledge of bioactive compounds produced by species of the Brazilian Cerrado biome.
Potencial bactericida de duas espécies típicas do cerrado brasileiro: Stryphnodendron obovatum e Lafoensia pacari
Keywords: bactericidal; Brazilian cerrado; extracts; herbal medicines; medicinal plants